Silase Berbahan Kulit Kopi sebagai Pakan Alternatif Berkelanjutan bagi Sapi Pedaging di Desa Wonomerto - Rahman, Arif Fadhil; Luthfiani, Puji; Muti, Annisa Rahma; Nurikhsan, Fajar Affan; Azzahra, Luthfiana; Zhafirah, Khansa Fitri; Irawan, Deni; Iskhan, Hani Gita Al; Baihaqi, Muhammad (Jurnal Pusat Inovasi Masyarakat, 2025)
This program aimed to enhance the knowledge and skills of livestock farmers in Wonomerto Village to produce coffee husk-based silages as an alternative feed for ruminants. The activities included collecting farmer information, preparing educational materials, conducting a silage-making demonstration, and evaluating knowledge improvement through pre-tests and post-tests. The results showed a significant increase in knowledge, with the average pre-test score of 86.25 rising to 93.75 in the post-test. A hedonic test indicated that coffee husk–based silage was well accepted by livestock, with an average palatability score of 2.75. The hedonic quality assessment showed that the color, aroma, and texture were all rated as good. Overall, the program successfully utilized coffee husk waste to produce high-quality alternative feed, supporting sustainable livestock farming and potentially improving the welfare of farmers in Wonomerto Village.